2019
DOI: 10.1108/prt-11-2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive pigments in coloured callus of Azadirachta indica for possible use as functional natural colourants

Abstract: Purpose: The purpose of this study is to evaluate the content of bioactive pigments in coloured callus of Azadirachta indica and to understand the correlation between the callus colours with their bioactive constituents, antioxidant properties and cytotoxicity. These assessments will yield valuable insight into the use of in vitro-derived pigments for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
4
4
1
Order By: Relevance
“…Based on the results, it was observed that green callus extract contained the highest level of AZA (214.53 ± 33.63 mg g -1 DW), followed by brown callus extract (51.56 ± 7.22 mg g -1 DW) and cream callus extract (28.49 ± 4.66 mg g -1 DW). These results are parallel to previously reported biochemical activities, which showed that green callus extracts possessed the highest bioactive compound content, antioxidant and cytotoxic potentials [38].…”
Section: Extraction and Quantification Of Azadirachtin (Aza) From Colsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results, it was observed that green callus extract contained the highest level of AZA (214.53 ± 33.63 mg g -1 DW), followed by brown callus extract (51.56 ± 7.22 mg g -1 DW) and cream callus extract (28.49 ± 4.66 mg g -1 DW). These results are parallel to previously reported biochemical activities, which showed that green callus extracts possessed the highest bioactive compound content, antioxidant and cytotoxic potentials [38].…”
Section: Extraction and Quantification Of Azadirachtin (Aza) From Colsupporting
confidence: 91%
“…Total AZA was extracted using absolute methanol, followed by liquid-liquid extraction using dichloromethane according to the protocol described by Singh and Chaturvedi [35]. We had previously reported that the colored callus of A. indica exhibits a wide range of biological actions such as radical scavenging and cytotoxic activities [38]. Due to these promising bioactivities, the colored callus obtained in this study (green, brown and cream) were evaluated for the presence of AZA, which is the most abundant bioactive compound of this species.…”
Section: Extraction and Quantification Of Azadirachtin (Aza) From Colmentioning
confidence: 99%
“…All extraction procedures were conducted in complete darkness. After homogenizing the samples, they were soaked in 60 mL of absolute methanol and incubated at 4 • C for 48 h. The filtrate was collected and stored at −20 • C. Re-extraction and filtration of the residue were performed and the extracts were combined and centrifuged for 5 min at 9000 rpm, 4 • C. A portion of these supernatants was immediately used for subsequent pigment analysis [80] to determine the total chlorophyll, carotenoid, and anthocyanin contents, while the remaining supernatants were concentrated to dryness using a rotavapor at 45 • C. The solvent-free extract was adjusted to a concentration of 10 mg/mL with absolute methanol and stored at −20 • C in an airtight glass vial until further analysis. The flow chart diagram of experimental outline is represented in Figure 3.…”
Section: Experimental Design and Sample Preparationmentioning
confidence: 99%
“…CM media consisted of 4.4 g of MS (Murashige and Skoog, 1962), 30 g/L of sucrose and 2 g/L of gelrite and supplemented with 0.6 mg/L TDZ, while MSO was similar to CM media but devoid of any plant growth regulators. The pH of both media (CM and MSO) were adjusted to 5.8 using 0.1 M NaOH or 0.1 M HCl (Ashokhan et al, 2018). The callus cultures were maintained in the culture room at 25 ± 2 • C with a 16 h photoperiod and 1000 lux of light intensity.…”
Section: Callus Induction and Proliferationmentioning
confidence: 99%
“…Meanwhile, the remaining portion of the supernatants were concentrated under reduced pressure at 60 • C using rotary evaporator (Rotavapor R-3 BÜCHI Labortechnik, 9230 Switzerland) to remove excess solvent. The resultant dried extracts were weighed and re-dissolved in absolute methanol to a concentration of 20 mg/mL and used for subsequent total phenolics, total flavonoids, phytochemical and antioxidants analysis (Ashokhan et al, 2018).…”
Section: Extraction Of Bioactive Pigments From Green Callus Of a Indicamentioning
confidence: 99%